Peran Otoritas Kristus Dalam Amanat Agung:Suatu Kajian Terhadap Teks Matius 28:18-20 - Eunike, Pratiwi; Dilham, Dilham (STT Pelita Dunia, 2025)
This article addresses the gap in theological understanding regarding the authority of Christ in the Great Commission (Matthew 28:18-20), which is often interpreted in abstract and universal terms, yet insufficiently connected to the social, cultural, and religious realities of Indonesia. Previous studies have primarily emphasized the global missiological aspects but frequently overlooked the integration of local values and the unique challenges faced by the Indonesian context. This study aims to comprehensively explore the theological significance of Christ's authority, identify its relevance for the Indonesian church, and formulate practical implications for the church’s mission. The method employed is a literature review using a contextual hermeneutical approach, combining historical, literary, and theological analyses of the biblical text with reflections on Indonesia's social, cultural, and religious dynamics. The findings reveal that the authority of Christ is not a static theological concept disconnected from worldly realities but rather a transformative power that empowers the church to carry out its mission in a relevant and contextual manner. This study also emphasizes the importance of a holistic understanding of the Great Commission, integrating spiritual, social, and ecological dimensions, so that the church’s mission becomes a participation in God's work of restoring creation. The article concludes with practical reflections on how the Indonesian church can embody the Great Commission with cultural sensitivity and prophetic courage.